2019
DOI: 10.2147/jhc.s222609
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatitis B And Hepatitis C Viral Infections And Associated Factors Among Patients With Diabetes Visiting Gondar Referral Teaching Hospital, Northwest Ethiopia: A Comparative Cross-Sectional Study</p>

Abstract: BackgroundThe liver is the major site of Hepatitis B virus and Hepatitis C virus replications. Patients with diabetes tend to be at an increased risk for developing various forms of liver diseases. The infection of the liver can cause or exacerbate diabetes. On the other hand, diabetes can cause or intensify the severity of liver infection. This comparative cross-sectional study was conducted with the aim to determine the prevalence of Hepatitis B and Hepatitis C virus infections and associated factors among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A total of 11 viruses were reported: HCV (43 studies) 10 , 24 – 60 , 82 , 84 , 86 , 88 , 89 , HBV (27 studies) 10 , 30 , 35 , 36 , 38 , 41 , 44 , 48 , 52 , 53 , 56 , 59 , 60 , 66 74 , 82 , 84 , 85 , HHV8 (8 studies) 12 , 61 65 , 81 , CMV (5 studies) 76 80 , SARS-CoV-2 (1 study) 83 , H1N1 virus (1 study) 87 , HSV1 (1 study) 75 , TTV (1 study) 37 , Parvovirus B19 (1 study) 79 , coxsackie B (1 study) 79 and HGV (1 study) 37 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 viruses were reported: HCV (43 studies) 10 , 24 – 60 , 82 , 84 , 86 , 88 , 89 , HBV (27 studies) 10 , 30 , 35 , 36 , 38 , 41 , 44 , 48 , 52 , 53 , 56 , 59 , 60 , 66 74 , 82 , 84 , 85 , HHV8 (8 studies) 12 , 61 65 , 81 , CMV (5 studies) 76 80 , SARS-CoV-2 (1 study) 83 , H1N1 virus (1 study) 87 , HSV1 (1 study) 75 , TTV (1 study) 37 , Parvovirus B19 (1 study) 79 , coxsackie B (1 study) 79 and HGV (1 study) 37 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 (12,13,14,15,16,17,18,19,21,22,23,24,25,26,27,28,29,30,31,32) studies were analyzed with 245,468,411 subjects were enrolled this study which were published between 2003 to 2020. In which divided into two subgroups, 12,982,158 patients with HBV infected group and 232,486,253 patients in non infected HBV groups.…”
Section: Figure 2 Outlines the Characteristics Of Included Studiesmentioning
confidence: 99%
“…14 Furthermore, the military is frequently mobile from place to place for different professional reasons and stays longer without their family, which may cause them to have multiple sex partners and increase their exposure to different sexually transmitted infections (STIs). 16 Several studies have reported the prevalence of HBV and HCV infections among different segments of the population in the study area [17][18][19][20][21][22][23][24] and there is a single report of armed forces in Bahir Dar, Amhara Regional State of Ethiopia. 16 No data were described the prevalence of viral hepatitis among military personnel in the study area.…”
Section: Introductionmentioning
confidence: 99%